Assessing the level of numeracy skills in type 1 diabetic children and their caregivers, and to ascertain an association with diabetes control - Moosa, Fatima Yakoub (My University, 2013)
Background: Health numeracy is an important component of diabetes care. Caregiver numeracy also impacts on diabetes outcomes. Hypothesis: Type 1 diabetic children with low numeracy will have poorer diabetes control (higher HbA1c levels). Aim: Assess the level of basic and diabetes-related numeracy in our type 1 diabetic children and their caregivers and to correlate this with diabetes control. Methods: A cross-sectional, questionnaire-based study was conducted in 53 type 1 diabetic children and 37 primary caregivers attending the CHBAH and CMJAH, between March and September 2009. Patient records were also accessed. The questionnaire was divided into 2 sections. Section 1 testing basic numeracy and section 2, testing diabetes- related numeracy. Data included the scores of the 2 sections, actual and ‘functional’ grades (grade level achieved on testing), HbA1c values and demographic data. Comparative analyses were used to assess the means of the percentage scores of both sections and actual versus ‘functional’ grades. Pearson correlation co-efficient ascertained the relationship between the test scores in each section with metabolic control. Results: The mean age of the children was 12.92 ± 2.96 years and the mean HbA1c level was 12.84 ± 3.04%. There were significant differences in the mean percentage scores for each section, (p<0.001 and <0.0001, children and caregivers respectively), with both groups performing better in section 1. Both groups performed equally poorly on the tasks of rounding, formulae and data interpretation. Significant correlation (r=0.345, p=0.014) was also found between the means of the actual grades and their ‘functional’ grades, with the ‘functional’ grade mean being lower in both groups. In addition, a significant negative correlation (r=-0.32, p=0.029) was found between the HbA1c levels and the section 2 scores. Conclusion: Both groups performed poorly in diabetes-related numeracy and performed below their actual grade potential. A significant relationship was also found between HbA1c levels and the diabetes-related numeracy scores, with participants who performed poorly having higher HbA1c levels. Recommendations: Interventional programmes need to incorporate numeracy assessment and training as a core component of diabetes education. Future research is however needed to determine the impact of such numeracy-focused interventions on diabetes outcome and metabolic control. Background: Health numeracy is important in diabetes care. Hypothesis: Type 1 diabetic children with low numeracy will have poorer diabetes control. Aim: Assess the level of basic and diabetes-related numeracy in our type 1 diabetic children and their caregivers and to correlate this with diabetes control. Methods: A cross-sectional sample of 53 type 1 diabetic children and 37 primary caregivers completed a basic maths and numeracy based questionnaire. HbA1c was also measured. Results: The mean age of the children was 12.92 ± 2.96 years and the mean HbA1c level was 12.84 ± 3.04%. Both groups performed better in basic maths than in numeracy (p<0.0001). A significant negative correlation (r=-0.32, p=0.029) was found between the HbA1c levels and the numeracy scores. Conclusion: Both groups performed poorly in diabetes-related numeracy and performed below their actual grade potential. A significant negative relationship was also found between HbA1c levels and the diabetes-related numeracy scores.